Reading development among elementary pupils at Payag Elementary School: Complexities and instructional implications - Shandylou B. Omongos; Cathy S. Taplac (Eureka: Journal of Educational Research, 2026)
This qualitative case study explored the complexities of reading development among elementary pupils at Payag Elementary School, a resource-constrained rural public school in Zamboanga del Sur, Philippines. Using semi-structured interviews with six reading teachers, the study examined factors influencing pupils’ reading development, teachers’ instructional responses, and potential strategies for improvement. Inductive thematic analysis revealed three major constraints affecting reading development: learner-related difficulties, socio-cultural factors, and resource limitations. Teachers responded through developmentally appropriate instruction, differentiated teaching strategies, and varied assessment practices. Findings further indicate the need for targeted professional development, improved instructional resources, and strengthened home–school collaboration. The study underscores the importance of context-sensitive, teacher-informed approaches to literacy development in rural Philippine schools.